THE EFFECT OF ALOE VERA COMPRESSES ON BREAST ENGORGEMENT PAIN IN POSTPARTUM MOTHERS - Safaah, Nurus; Erna Eka Wijayanti; Umu Qonitun (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Breast engorgement is an unpleasant physiological condition characterized by swelling and pain in the breasts. Treatment to reduce breast engorgement uses aloe vera which contains aloin and emodin which can function as analgesics. The purpose of this study was to determine the effect of aloe vera compresses on breast engorgement in postpartum mothers. Methods: This was a true-experimental design with a pre-post test design with a control group. The independent variable is Aloe vera compress while the dependent variable is Breast engorgement pain. The population in this study were all postpartum mothers at the Merakurak health center, The sample in this study was 32 postpartum mothers at the Merakurak Community Health Center who met the inclusion criteria, The sampling technique used consecutive sampling and data collection using observation sheets involving 32 postpartum mothers. The statistical tests were undertaken using the Wilcoxon and Mann-Whitney tests. Results: The results of the study showed that the majority of postpartum mothers were aged 20-35 years, in a total of 23 mothers (93.6%). Most of them (62.5%) had a high school educational background, and most of them (62.5%) had a history of multiparas. Based on the results of the study, there is an effect of giving aloe vera compresses on breast engorgement in postpartum mothers (p-value 0.000). Conclusion: Aloe vera compress therapy can be used by postpartum mothers to treat breast milk retention because aloe vera contains anthraquinone which contains aloin and emodin which can function as analgesics. Aloe vera compress can be done Recommended as a complementary therapy for breast engorgement pain.